Asymmetric-bifurcation snapping, all-or-none motion of Venus flytrap - Xiangli Zeng; Yingzhe Wang; Keisuke Morishima (Scientific Reports)
Abstract The Venus flytrap is a carnivorous plant that catches insects by snapping rapidly and reopening slowly. To understand the mechanism underlying this asymmetrically reversible motion, a three-dimensional laser profiler was used to measure both static morphological information and dynamic movements (500 frames per second) of the Venus flytrap, including its rapid closure and slow re-opening. The mean-curvature differences between the open and closed lobes were recorded and used for morphology and energy evaluations. The effects of geometric parameters such as the length, width, height, and thickness of the lobes on the closing time were analyzed, and the all-or-none motion of the Venus flytrap was examined. Moreover, a mathematical asymmetric-bifurcation buckling model was developed. The Venus flytrap has asymmetric energy states for the closing and opening conditions; therefore, storage of a larger amount of energy makes the re-opening motion slower. These pre-programmed movements of plants can facilitate the development of more intelligent soft robots.